Ca4Au10Zn3 – A Substitution Variant of AlB2 by Incorporation of Zn3 Triangles1. Issue 12 (27th August 2015) - Gerke, Birgit; Hoffmann, Rolf‐Dieter; Pöttgen, Rainer
Abstract: The gold‐rich intermetallic phase Ca4 Au10 Zn3 was synthesized from the elements by high‐frequency melting in sealed tantalum ampoules. Analyses of the sample by X‐ray powder and single crystal diffraction indicated a new structure type with a small homogeneity range resulting from Au/Zn mixing: C 2/ c, a = 1598.4(2), b = 819.7(1), c = 1188.2(2) pm, β = 120.93(1)°, wR 2 = 0.0397, 2292 F 2 values, 83 variables for Ca4 Au9.66(1) Zn3.34(1), and a = 1596.6(2), b = 818.8(2), c = 1187.1(2) pm, β = 120.91(2)°, wR 2 = 0.0280, 2296 F 2 values, 83 variables for Ca4 Au9.98(1) Zn3.02(1) . The gold atoms built up a three‐dimensional distorted tetrahedral network with Au–Au distances ranging from 274–294 pm. The cavities within this network are filled by calcium atoms and Zn3 triangles (272–279 pm Zn–Zn) in an ordered manner. The small homogeneity range Ca4 Au10– x Zn3+ x concerns Au/Zn mixing within the triangles and the tetrahedral network as well. The crystal chemical relationship with the aristotype AlB2 is discussed on the basis of a group‐subgroup scheme. Abstract :